Facial Angioedema after the first dose of Covishield (adenovirus-vectored severe acute respiratory syndrome coronavirus 2 vaccine): follow-up after the second and third booster doses - Walter de Araujo Eyer-Silva; Lidiane Simões de Carvalho Paes Leme (Revista da Sociedade Brasileira de Medicina Tropical, 2022)
ABSTRACT Mass vaccination campaigns are essential to control the ongoing novel severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) pandemic. The Covishield vaccine consists of the replication-deficient simian adenovirus vector ChAdOx1, which contains the full-length structural spike protein of SARS-CoV-2. Occasionally, it can lead to cutaneous reactions that contribute to fear of vaccination, hesitancy, and incomplete vaccination schedules. We report a case of facial angioedema following the first dose of Covishield in a 63-year-old woman with no previous history of allergies or hypersensitivity to drugs or vaccines. No rebound of angioedema was recorded after the second homologous and third heterologous doses.